2022
DOI: 10.3389/fpubh.2022.992555
|View full text |Cite
|
Sign up to set email alerts
|

How meteorological factors impacting on scrub typhus incidences in the main epidemic areas of 10 provinces, China, 2006–2018

Abstract: Scrub typhus, caused by Orientia tsutsugamushi, is a serious public health problem in the Asia-Pacific region, threatening the health of more than one billion people. China is one of the countries with the most serious disease burden of scrub typhus. Previous epidemiological evidence indicated that meteorological factors may affect the incidence of scrub typhus, but there was limited evidence for the correlation between local natural environment factors dominated by meteorological factors and scrub typhus. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…In addition, this study also indicated that increased monthly minimum temperature could lead to high risk of the occurrence of scrub typhus. This result is consistent with previous study showing that mite activity decreases when the temperature drops below 10°C ( 21 ). In southern Yunnan, L. deliense is the summer-autumn type, with the highest numbers in July ( 38 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In addition, this study also indicated that increased monthly minimum temperature could lead to high risk of the occurrence of scrub typhus. This result is consistent with previous study showing that mite activity decreases when the temperature drops below 10°C ( 21 ). In southern Yunnan, L. deliense is the summer-autumn type, with the highest numbers in July ( 38 ).…”
Section: Discussionsupporting
confidence: 94%
“…Female mites mainly deposit their eggs from March to May, with egg-laying rates decreasing when the temperature ranges rise between 25 and 30°C ( 30 ). The optimal temperature for larva hatching and development is above 22°C, and temperatures between 18 and 30°C are conducive for mites to seek hosts for pathogen transmission ( 21 , 30 , 35 , 36 ). Adult mites remain in the soil for at least 15 months, while the larva stage can survive several months until the appropriate temperature for feeding ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Without appropriate treatment, the mortality rate of patients with ST may be as high as 30–70%, while the median mortality rate of untreated patients is 6%, compared to 1.4% for those who receive treatment [ 5 ]. In China, scrub typhus is mainly endemic in the north, south and southwest of the country [ 6 ], which includes the Guangdong, Yunnan, Anhui, Guangxi, Fujian, Jiangsu, Shandong and Jiangxi provinces [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence rate of scrub typhus in Jiangxi Province from 2006 to 2012 demonstrated a consistent upward trend [ 12 ]. Additionally, there were a total of eight provinces in mainland China that reported more than 5000 cases of scrub typhus between 2006 and 2018, with Jiangxi Province being one of them [ 13 ]. Since the first case was reported in Ganzhou City in 2006, the disease has been spreading, making it a high prevalence area for scrub typhus in Jiangxi Province [ 14 ].…”
Section: Introductionmentioning
confidence: 99%